Assessing the Impact of the Factors in the Digital Transformation on the Regional Economic Growth - Tatyana V. Mirolubova (National Research Mordova State University, 2021)
Introduction. The scientific problem under consideration is of particular relevance due to the need to assess the impact of the factors in the digital transformation of the regional economy and in the economic growth on the economic development of the regions of the Russian Federation. Based on the research conducted, the article presents an econometric assessment of the dependence of the level of the gross regional product per capita in the regions of Russia on such factors as digital labor and digital capital.